Green Accounting and Its Implementation in Indonesia - Andi, K. Petta Lolo, Arjuni; Alimuddin; Hamid Habbe; Mediaty; Andi, Maulana K. (Efektor, 2020)
The growth of industrial world is an undeniable problem in the environment where industrial behavior often ignores impacts on the environment, such as water, soil, air pollution and social inequality in the environment. The purpose of this study is intended to determine the role of green accounting in reducing environmental pollution and to examine the extent to which the application of green accounting in Indonesia in supporting sustainability. This study uses an interpretive approach which focus on the subjective nature of social world and tries to understand it. Green accounting has difficulty measuring the value of costs and benefits of externalities arising from industrial processes. It is not easy to measure the loss to people around and the ecological environment caused by air pollution, liquid waste, ammonia tube leakage, nuclear tube leakage or other externalities. Unfortunately, in its application, often some companies do not report bad news they are facing, so reporting on environmental costs is not effective.